Pemberdayaan IPM Melalui Perpustakaan Mini Sebagai Upaya Meningkatkan Produktivitas Baca-Tulis di Kapas Madya Baru Surabaya - Ridlwan, M.; Asyari, Asyari (Universitas Muhammadiyah Surabaya, 2017)
Library is the most important thing in sharpening youth knowledge. So as a strategy in order to form productivity mabaca and nenulis juveniles. Because adolescents with their sensitivity are very sensitive to the environment so it triggers the juvenile delinquency. Therefore, this dedication is carried out during the one-month time allocation through the procurement of multi-source mini libraries that are established through the form of training or workshops that are teenagers strategic in the formation of the growth of literacy productivity. The results obtained show that the formation of reading and writing culture through multi-source library conducted with the guidance of inten. Workshops or reading and writing skills can make it easier for youth IPM to give creativity and innovation. So denagan kegitan like that a bit much can minimize juvenile delinquency. Therefore, the need to hold a mini library in a mosque with activities of literacy and adolescent literacy should be done in a sustainable manner.